2016
DOI: 10.1007/978-3-319-28591-7_5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Impact Assessment Methodology for Evaluating Distributional Impacts in Scottish Climate Change Adaptation Policy

Abstract: While it is widely recognised that the impacts of both climate change and the policy response will be distributed, there is an absence of complete information regarding the socio-economic and geographic patterning of such impacts in the intra-national context. This paper seeks to address this gap, presenting a climate justice toolkit (indicator set and guidance) that enables the consistent assessment of distributional impacts of climate policy, and thus allows cumulative impacts to be assessed across the broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For example, increasing deprivation and exclusion caused by societal status and the impacts of climate change may also impact on people's ability to be included and participate in decision-making. Accordingly, research has shown that those who are most likely to be affected by climate change are also those who are usually excluded and less able to participate in decision-making, and therefore further reducing their capacity to adapt to extreme events (Lindley et al, 2011;Dunk et al, 2016;Tan et al, 2015). In that sense, concerns of recognition and participation are interrelated in our case, hence we analyse these issues together (also following Martin et al, 2013Martin et al, , 2015.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, increasing deprivation and exclusion caused by societal status and the impacts of climate change may also impact on people's ability to be included and participate in decision-making. Accordingly, research has shown that those who are most likely to be affected by climate change are also those who are usually excluded and less able to participate in decision-making, and therefore further reducing their capacity to adapt to extreme events (Lindley et al, 2011;Dunk et al, 2016;Tan et al, 2015). In that sense, concerns of recognition and participation are interrelated in our case, hence we analyse these issues together (also following Martin et al, 2013Martin et al, , 2015.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 98%
“…In particular, there are still gaps on how climate adaptation responses consider disaggregated impacts and socially just outcomes amid pre-existing social inequality. It is thus necessary to consider that besides the direct impacts of climate change, adaptation responses too can be unevenly distributed and unequally shared (Dunk et al, 2016;Lindley et al, 2011;Marino & Ribot, 2012).…”
Section: Indicatormentioning
confidence: 99%